Heterologous prime-boost immunisation with mRNA- and AdC68-based 2019-nCoV variant vaccines induces broad-spectrum immune responses in mice - Li, Xingxing; Liu, Jingjing; Li, Wenjuan; Peng, Qinhua; Li, Miao; Ying, Zhifang; Zhang, Zelun; Liu, Xinyu; Wu, Xiaohong; Zhao, Danhua; Yang, Lihong; Cao, Shouchun; et al. (Frontiers in Immunology, 2023)
The continuous emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants has been associated with the transmission and pathogenicity of COVID-19. Exploring the optimal immunization strategy to improve the broad-spectrum cross-protection ability of SARS-CoV-2 variant vaccines is of great significance. Herein, we evaluated different heterologous prime-boost strategies with chimpanzee adenovirus vector-based SARS-CoV-2 vaccines with the Wuhan-Hu-1 strain (AdW) and Beta variant (AdB) and mRNA-based SARS-CoV-2 vaccines with the Wuhan-Hu-1 strain (ARW) and Omicron variant (ARO) in six-week-old female BALB/c mice. AdW and AdB were administered either intranasally or intramuscularly, and ARW and ARO were administered intramuscularly. Intranasal or intramuscular vaccination with AdB followed by ARO booster exhibited the highest levels of cross-reactive IgG, pseudovirus-neutralizing antibody (PNAb) responses, and angiotensin-converting enzyme-2 (ACE2) -binding inhibition rates against different SARS-CoV-2 variants among all vaccination groups. Moreover, intranasal AdB vaccination followed by ARO induced higher levels of IgA and neutralizing antibody responses against live SARS-CoV-2 than intramuscular AdB vaccination followed by ARO. A single dose of AdB administered either intranasally or intramuscularly induced broader cross-NAb responses than AdW. A Th1-biased cellular immune response was induced in all vaccination groups. Intramuscular vaccination-only groups exhibited higher levels of Th1 cytokines (IFN-γ, IL-2, and TNF-α) than intranasal vaccination-only and intranasal vaccination-containing groups. There were no significant differences between the Th2 cytokine levels (IL-4 or IL-10) in all vaccination groups and the control group. This study provides reference data for assessing vaccination strategies for different SARS-CoV-2 variant vaccines to achieve high broad-spectrum immune efficacy.